(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Impersonal sentences in English play a crucial role in communication, allowing speakers to convey information without specifying an agent. These constructions are frequently used in formal, academic, and scientific discourse, where objectivity and depersonalization are required. Linguistic theories, including traditional grammar, structuralism, transformational-generative grammar, and cognitive-functional linguistics, provide different perspectives on their structure and usage. This article examines these approaches, analyzing their contributions to the study of impersonal sentences. By combining syntactic, cognitive, and functional insights, this study highlights the significance of impersonal constructions in effective communication.